Two-stage screening for early dementia in primary care. Issue 9 (20th October 2016) - Grober, Ellen; Mowrey, Wenzhu Bi; Ehrlich, Amy R.; Mabie, Peter; Hahn, Steven; Lipton, Richard B.
ABSTRACT: Objective : The objective was to compare two screening strategies for dementia in an urban primary care clinic, serving a low-education, minority community composed largely of Latino and African American patients. Method : Two hundred and fifty-seven patients underwent two-stage patient-based screening (PBS) and informant-based screening (IBS) followed by a diagnostic evaluation. In the first stage, PBS included brief tests of episodic memory (Memory Impairment Screen), semantic memory (Animal Fluency), and executive function (Reciting Months Backwards). For IBS, the first stage consisted of the short Informant Questionnaire on Cognitive Decline in the Elderly, administered to a family member or friend. Patients who screened positive in the first stage of either strategy underwent testing with the picture version of the Free and Cued Selective Reminding Test with Immediate Recall to identify memory impairment. Sensitivity, specificity, and positive and negative predictive values were computed for various cutoffs of each test and combination of tests. Dementia was diagnosed using Diagnostic and Statistical Manual of Mental Disorders–Fourth Edition ( DSM–IV ) criteria without access to the screening test results. Results : We identified 66 patients (25.7%) with previously undiagnosed dementia. Sensitivity was the same (77%) for both strategies but specificity was higher for IBS than for PBS (92% versus 83%). IBS's higher specificity makes it the preferred strategy if a knowledgeable informant is available. Conclusion : Unrecognized dementia is common in primary care. Case-finding can be improved using either PBS or IBS two-stage screening strategies.